Support for Propaganda: Chinese perceptions of public service advertising. - Esarey, Ashley; Stockmann, Daniela; Zhang, Jie (Journal of Contemporary China, 2017)
This article examines Chinese perspectives of, and support for propaganda, relying on television public service advertisements as a means of tapping into citizens’ beliefs. Through the analysis of data from focus groups conducted in Beijing and public opinion survey data from 30 cities, this study argues that Chinese people are generally supportive of state efforts to guide public attitudes through television advertisements, although levels of support vary by age, education and gender. The study suggests that considerable popular support for state propaganda contributes to the regime’s capacity to guide public opinion and helps to explain the persistence of popular support for authoritarian rule.